A comparison of the self‐reported dry eye practices of New Zealand optometrists and ophthalmologists. (17th February 2017) - Xue, Ally L.; Downie, Laura E.; Ormonde, Susan E.; Craig, Jennifer P.
Abstract: Purpose: The aim of this cross‐sectional survey was to evaluate the self‐reported clinical practices of New Zealand optometrists and ophthalmologists with respect to the diagnosis and management of dry eye disease. It also sought to compare these behaviours with the current research evidence base. Methods: An anonymous survey was distributed electronically to New Zealand eye care clinicians (optometrists n  = 614, ophthalmologists n  = 113) to determine practitioner interest in dry eye disease, practice experience, practice modality, preferred diagnostic and management strategies, and information used to guide patient care. Results: Respondents from both professions (response rates, optometrists: 26%, ophthalmologists: 26%) demonstrated similarly strong knowledge of tear film assessment. Ninety percent of respondents ranked patient symptoms and meibomian gland evaluation as the most valuable and common diagnostic approaches. Conversely, standardised grading scales and validated dry eye questionnaires were infrequently adopted. Both professions tailored dry eye management according to severity, indicating eyelid hygiene and non‐preserved lubricants as mainstay therapies. Ophthalmologists prescribed systemic tetracyclines significantly more often than optometrists for moderate (48% vs 11%) and severe (72% vs 32%) dry eye ( p  <   0.05). Continuing education conferences were acknowledged as the primary information source used to guide dry eye management practices by both professions. Conclusions: Consistent with evidence‐based guidelines, New Zealand eye care professionals combine subjective and objective techniques to diagnose and stratify dry eye management according to disease severity. There is potential to improve dissemination of research evidence into clinical practice, with continuing education via professional conferences the favoured mode of delivery.